Pembangunan Sistem Streaming untuk Ibadah Daring sebagai Solusi Penyelenggaraan Ibadah di Masa Pandemi Covid-19 di GKI Tegalrejo Salatiga - Suharyadi Suharyadi; Teguh Wahyono; Irwan Sembiring; Agus Sugiarto; Adriyanto Juliastomo Gundo (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2021)
The COVID-19 pandemic has caused many activities that require face-to-face contact cannot be carried out directly, including for the needs of Sunday Worship at GKI Tegalrejo Salatiga. To facilitate this, it is necessary to develop an daring worship system that is carried out live streaming. This activity aims to build the streaming system so that the worship performed at the church can also be followed by the congregation directly from their respective homes. The program implementation method is carried out in six steps, namely identification of needs and mapping of existing conditions, planning and priority scale, setting of streaming equipment, training, implementation, and the last is evaluation.